2021
DOI: 10.3390/cancers13122918
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Embryonal Sarcoma of the Liver in Children Versus Adults: A National Cancer Database Analysis

Abstract: This study evaluates the clinicopathological characteristics and outcomes of children vs. adults with undifferentiated embryonal sarcoma of the liver (UESL). A retrospective analysis of 82 children (<18 years) and 41 adults (≥18 years) with UESL registered in the National Cancer Database between 2004–2015 was conducted. No between-group differences were observed regarding tumor size, metastasis, surgical treatment, margin status, and radiation. Children received chemotherapy more often than adults (92.7% vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…It accounts for approximately 9-13% of primary liver tumors in children [3]; however, it is extremely rare in adults, accounting for approximately 0.2% of the primary liver tumors [4]. Furthermore, UESL has a worse prognosis in adults, with a 5-year overall survival (OS) rate of 48.2% compared to 84.4% in children [5,6]. The standard treatment strategy for UESL has not been established, and there is no drug for the treatment of UESL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It accounts for approximately 9-13% of primary liver tumors in children [3]; however, it is extremely rare in adults, accounting for approximately 0.2% of the primary liver tumors [4]. Furthermore, UESL has a worse prognosis in adults, with a 5-year overall survival (OS) rate of 48.2% compared to 84.4% in children [5,6]. The standard treatment strategy for UESL has not been established, and there is no drug for the treatment of UESL.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment strategy for UESL has not been established, and there is no drug for the treatment of UESL. However, recent studies have shown that margin-negative resection improves the OS [5,6]. Currently, most patients receive vincristine, actinomycin-D, cyclophosphamide (VAC), or ifosfamide based on the Intergroup Rhabdomyosarcoma Study protocol [7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is uncertain how the Pre‐Treatment Extent of Disease (PRETEXT) system, which has been globally implemented as a reliable risk stratification and surgical decision‐making tool for hepatoblastoma, 13,14 applies to UESL. Given the discrepancies in the literature regarding the impact of complete resection on survival, often leading to decision‐making challenges regarding conventional resection versus liver transplantation for patients with UESL, the PRETEXT system holds promise as a decision aid in this distinct pathology 9,15 …”
Section: Introductionmentioning
confidence: 99%
“…Metastases are present in most patients at the time of initial diagnosis, most often in the lung (2,3), pleural and peritoneal regions, and occasionally epidural and subcutaneous zones (4). The Surveillance, Epidemiology, and End Results (SEER) database analysis showed that UESL in adult patients mainly affected males, and the prognosis was significantly worse than that in children (5); the risk of death was significantly higher for adults than pediatric patients (6). The right lobe of the liver is a common site for UESL (7).…”
Section: Introductionmentioning
confidence: 99%